Western Australian Radiology Departments’ Views on Australian Personally Controlled Electronic Health Record - Tait, O.; Horne, M.; Lo, C.; Evans, A.; Ng, Curtise Kin Cheung (The Society of Radiographers of South Africa, 2016)
Introduction: Since the last decade, many countries have started developing a national electronic health record (EHR). The national EHR in Australia is called Personally Controlled Electronic Health Record (PCEHR). It has been available for use since 1 July 2012. A federal government’s review of its implementation was conducted in late 2013 because it failed to meet the set targets. The purpose of this study was to investigate Western Australian radiology departments’ views on the PCEHR complementary to the government’s review report. Methods: Chief medical imaging technologists (n=18) and picture archiving and communication system (PACS) administrators (n=18) from public and private hospitals in Western Australian were invited to participate in this study in May 2014. The response rate for participation was 22.2 percent (8/36). Semi-structured interviews were conducted with the participants to obtain their perceptions of PCEHR. The interviews were analysed inductively and thematically. Results: There were eight people (n=8) who agreed to participate. They believed the PCEHR would enhance efficiency and effectiveness of healthcare services if barriers to its implementation were addressed. The major barriers identified were concern of individual privacy, increase of staff workload, inadequate system functionalities and training, lack of involvement of stakeholders and money. The use of Medicare to provide both positive and negative incentives to the stakeholders was suggested as a viable solution to address the current barriers. Conclusion: This study investigated four Western Australian radiology departments’ perceptions of PCEHR. Although their perceptions were similar to the ideas in the government’s review report in general, new insights were also provided by the participants. These findings could potentially complement the government’s review.